The Assessment of Radon Emissions as Results of the Soil Technogenic Disturbance - Leshukov, Timofey (Int J Environ Res Public Health, 2020)
(222)Rn is a specific indoor-type pollutant that represents a primary radiological hazard as a main source of ionizing radiation (IR) for humans. Coal mining creates new sources of gas that are formed over mines. This process can significantly increase the density of radon flux. Therefore, the concentration of radon in a room can increase. We investigated the territory of the Leninsk-Kuznetsky district of the Kemerovo region, which is subject to underground mining. Two groups of residential locations and measuring points of radon flux density were selected to identify the higher emanation relationship of radon and mining-affected areas. The first group (Case group) included subjects located within the territory of the underground mine; the other (Control group) included subjects in an area without mining. Radon flux density in coal mining areas was significantly higher than in the rest of the territory; moreover, the percentage of values in the Case group that had a radon flux density above 80 mBq·m(−2)·s(−1) was 64.53%. For the Case group, 20.62% of residential buildings had a radon concentration above 200 Bq/m(3). For the studied area, the radon flux density correlates positively (r = 0.79, p = 0.002) with indoor radon. Additional clastogenic/aneugenic effects are also found in dwellings with increased volume activity of radon (VAR) within the territories of underground mines. Ring chromosomes are positively correlated with radon levels in smoker groups but not in non-smokers. An increased frequency of binucleated (BN) cells with micronuclei (MN) is also positively correlated with VAR regardless of smoking status. It has been concluded that reducing the total exposure level of a population to radon can be achieved by monitoring areas with underground mines where radon is emitted heavily.